KEBIJAKAN REMUNERASI PEGAWAI NEGERI SIPIL (Analisis Materi Muatan Penentuan Nilai dan Kelas Jabatan dalam Pemberian Remunerasi) - Nayla Alamiya; Aryuni Yuliatiningsih; Tedi Sudrajat; Dessy Perdani YurisPS (Faculty of Law, Universitas Jenderal Soedirman, 2013)
Aryuni Yuliantiningsih, Tedi Sudrajat dan Dessi Perdani Yuris Puspita SariFakultas Hukum Universitas Jenderal Soedirman PurwokertoE-mail:Good or bad of a state bureaucracy is strongly influenced by the quality of its service. It means that the bureaucracy sector and policy in order to reform of bureaucracy needs to be a focus of study. One of the policies that can support the performance and welfare in the creation of good public service is going to be the remuneration policy. However, until 2012, the remuneration policy has not been implemented throughout the institution/agency. The determination of the value and class policy positions that have been implemented have diverse forms of regulation. Keywords: bureaucracy reformation, remuneration, value and class positions